Efficacy of tramadol and butorphanol pretreatment in reducing pain on propofol injection: A placebo-controlled randomized study - Arvinderpal Singh; Geeta Sharma; Ruchi Gupta; Anita Kumari; Deepika Tikko (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Pain of propofol injection has been recalled by many patients as the most painful part of the induction of anesthesia. Tramadol and butorphanol are commonly used analgesics for perioperative analgesia in anesthesia practice. However, their potential to relieve propofol injection pain still needs to be explored. Material and Methods: A randomized, double-blind, placebo-controlled study was conducted on 90 American Society of Anesthesiologists I and II adult patients undergoing elective surgery under general anesthesia with propofol as an induction agent. Consecutive sampling technique with random assignment was used to allocate three groups of 30 patients each. Group I patients received an injection of normal saline 3 ml intravenously (placebo) while Group II and Group III patients received injection of tramadol 50 mg and butorphanol 1 mg intravenously, respectively. Before induction of anesthesia patients were asked about the intensity of pain on propofol injection by using visual analog scale (VAS) before the loss of consciousness. Descriptive statistics and analysis of variance with Chi-square test were used to analyze the data. The value of P < 0.05 was considered as a significant and P < 0.0001 as highly significant. Results: The incidence of pain in Group I was observed in 80% of the patients, while it was observed in 23.33% and 20% of patients in Group II and III, respectively. Mean VAS scores were 2.27 ± 1.51, 1.14 ± 1.74, and 1.03 ± 1.72 in Group I, II, and Group III patients, respectively. The incidence of pruritus was 10% and 6.7% and erythema in 13.2% and 6.7% in Group II and III, respectively. Conclusion: Pretreatment with both butorphanol and tramadol significantly reduced pain on propofol injection; however, they exhibited comparable efficacy among each other. Thus, either of these two drugs can be considered for pretreatment to reduce propofol injection pain.